2021
DOI: 10.7150/jca.58580
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Non-Randomized Study of Intraoperative Assessment of Surgical Resection Margin of Colo-Rectal Liver Metastases

Abstract: Introduction: More than 50% of patients with colorectal cancer (CRC) develop liver metastases during the natural course of disease. Surgical resection is currently the most potentially curative method in the treatment of colorectal liver metastases (CRLM). The goal of surgery is to achieve a negative resection margin (RM) of at least 1 mm, which provides the best prognosis for patients. The RM can be assessed by the pathologist of the resected liver specimen (RLS) and by the surgeon intraoperatively. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
3
0
1
Order By: Relevance
“…Some authors have recently suggested that intraoperative assessment of resection margins could be clinically meaningful, and that margin re-resection could be indicated in selected cases. 28,29 Although in our series R1-contact was associated with poorer outcomes compared to R1 < 1 mm, it is difficult to draw any conclusion on whether intraoperative or postoperative margin reresection could improve the outcome. In fact, only two patients recurred with isolated surgical bed recurrence, and they belonged to the R1-contact group.…”
Section: Survival Outcomesmentioning
confidence: 64%
“…Some authors have recently suggested that intraoperative assessment of resection margins could be clinically meaningful, and that margin re-resection could be indicated in selected cases. 28,29 Although in our series R1-contact was associated with poorer outcomes compared to R1 < 1 mm, it is difficult to draw any conclusion on whether intraoperative or postoperative margin reresection could improve the outcome. In fact, only two patients recurred with isolated surgical bed recurrence, and they belonged to the R1-contact group.…”
Section: Survival Outcomesmentioning
confidence: 64%
“…It was believed that increasingly efficient chemotherapy may have changed the long-term outcome after a R1 resection, especially in patients with advanced metastatic disease [ 6 , 16 ]. A series of studies have testified and showed benefit of modern chemotherapy on R1 resection that there were no negative impacts in survival rates, particularly in patients with optimal morphological or major histopathological responses [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, intraoperative decision-making by the individual surgeon will still have impact on the probability to perform a curative resection. Protic et al 18 assessed patients undergoing surgery for colorectal liver metastasis and intraoperative assessment of resection margins by an experienced hepatobiliary surgeon improved the prognostic impact on recurrence rate and disease-free survival compared to standard postoperative histopathological assessment by a pathologist. In the present study, patients with pathological Stages 0-2 had better overall survival than patients where the operating surgeon had deemed the operation curative.…”
Section: Discussionmentioning
confidence: 99%